Digestion of Plant Dietary miRNAs Starts in the Mouth under the Protection of Coingested Food Components and Plant-Derived Exosome-like Nanoparticles - Qin, Xinshu; Wang, Xingyu; Xu, Ke; Zhang, Yi; Ren, Xiaoyu; Qi, Bangran; Liang, Qian; Yang, Xingbin; Li, Lin; Li, Shiqi (Journal of agricultural and food chemistry, 2022)
The regulatory functions of plant miRNAs on mammalian bodies are controversial, mainly because stability of the miRNAs in the digestive tract, as the prerequisite for their cross-kingdom effects, has somehow been overlooked. Hence, as the first stage of food ingestion, stability of plant miRNAs in human saliva has been investigated. The results show that plant miRNAs are of considerable resistance against salivary digestion, as surviving miRNAs more than 20 fM are detected. The stability varies dramatically, which can be explained by the difference in tertiary structure, governing their affinities to RNase. Surprisingly, miRNAs of low initial concentrations can end up with high survival rates after digestion. Plant miRNAs can be loaded into exosome-like nanoparticles (ELNs) and microcapsules formed by food components, both of which protect the miRNAs from being degraded in human saliva. Overall, plant miRNAs can apply certain strategies to maintain constant concentrations, paving the way for their potential cross-kingdom effects.